TypeLoader: A fast and efficient automated workflow for the annotation and submission of novel full‐length HLA alleles. (14th May 2017) - Surendranath, V.; Albrecht, V.; Hayhurst, J. D.; Schöne, B.; Robinson, J.; Marsh, S. G. E.; Schmidt, A. H.; Lange, V.
Abstract : Recent years have seen a rapid increase in the discovery of novel allelic variants of the human leukocyte antigen (HLA) genes. Commonly, only the exons encoding the peptide binding domains of novel HLA alleles are submitted. As a result, the IPD‐IMGT/HLA Database lacks sequence information outside those regions for the majority of known alleles. This has implications for the application of the new sequencing technologies, which deliver sequence data often covering the complete gene. As these technologies simplify the characterization of the complete gene regions, it is desirable for novel alleles to be submitted as full‐length sequences to the database. However, the manual annotation of full‐length alleles and the generation of specific formats required by the sequence repositories is prone to error and time consuming. We have developed TypeLoader to address both these facets. With only the full‐length sequence as a starting point, Typeloader performs automatic sequence annotation and subsequently handles all steps involved in preparing the specific formats for submission with very little manual intervention. TypeLoader is routinely used at the DKMS Life Science Lab and has aided in the successful submission of more than 900 novel HLA alleles as full‐length sequences to the European Nucleotide Archive repository and the IPD‐IMGT/HLA Database with a 95% reduction in the time spent on annotation and submission when compared with handling these processes manually. TypeLoader is implemented as a web application and can be easily installed and used on a standalone Linux desktop system or within a Linux client/server architecture. TypeLoader is downloadable fromhttp://www.github.com/DKMS‐LSL/typeloader .